Benchmarking Regulators : Making Telecom Regulators More Effective in the Middle East - Mustafa, Mohammad A. (World Bank, Washington, DC, 2012)
Like telecommunications reformers elsewhere, Arab countries have set up independent regulatory authorities to make objective, consistent, and non-arbitrary regulatory decisions. This is a major step forward and is already delivering positive results for consumers in the form of new and better telecommunications services. Still, some governments seem reluctant to hand over the regulatory role, limiting the effectiveness of sector regulation and the agencies formed to implement it. One way forward is through benchmarking-to help policymakers and potential investors assess regulatory performance and prioritize efforts to strengthen it.